Molecular Mechanism of Integrin αvβ6 in Liver Metastasis of Colon Cancer Based on SDF-1/CXCR4 - Shi, Jinglong; Fan, Ludi; Li, Bo; Pan, Hui (Cellular and Molecular Biology, 2022)
With the changes in people's dietary life, the incidence and mortality of colon cancer have risen sharply. Invasive metastasis of colon cancer is the main reason affecting the prognosis. Therefore, it is very important to study the molecular mechanism of SDF-1/CXCR4 and integrin αvβ6 in liver metastasis of colon cancer. Floating cells were used to detect the appearance of β6, and the relationship between SDF-1/CXCR4 and the molecular mechanism of colon cancer redirection was analyzed. Use immunohistochemistry to detect the appearance of SDF-1/CXCR4 and αvβ6 protein, and combine the data with clinical-pathological data for statistical analysis. Experimental data showed that the positive expression rates of αvβ6 protein in well-differentiated and poorly differentiated colon cancer tissues were 21.4% and 30.6%, respectively, and the difference was statistically significant (P<0.01). The results show that the appearance of SDF-1/CXCR4 in colon cancer cells (CCC) has nothing to do with the type of cancer cells, and increases with the decrease of cell differentiation. This has a great relationship with the classification of the clinical TNM disease stage. The later the disease stage, the higher the expression level. The αvβ6 has a strong correlation with the invasion and metastasis of colon cancer and can be used as a criterion for judging liver metastasis and prognosis.